Acute tonsillitis and pediatric functional gastrointestinal disorders: the first result of a possible association analysis - E. R. Meskina; L. A. Galkina; T. V. Stashko (Детские инфекции (Москва))
Acute tonsillitis (AT) and functional disorders of the digestive system (FDDS) are widespread among children. There is insufficient information about whether FDDS affects the incidence and course of АT, or whether АT may predispose to the development of АT. The aim is to discover a possible relationship between acute exudative tonsillitis and FDDS in children in the context of clinical and medico-social assessment. Materials and Methods: An observational cross-sectional study was performed using the continuous sampling method. There were 137 patients under observation, aged from one to 18 years, hospitalized in a hospital with АT, proceeding with overlaps on the tonsils, including 44 children younger and 93 older than 4 years. Bacterial АT was diagnosed on the MacIsack scale (≥ 4 points) in combination with the determination of inflammatory markers (leukocytosis, CRP). Epstein-Barr viral etiology of АT was diagnosed based on the detection of anti-EBV-VCA IgM and/or anti-EBV-EA IgG in the absence of anti-EBV-NA IgG. The legal representatives of the children agreed to participate in the study and completed a developed questionnaire containing 41 questions to assess medical and social factors, health status and gastrointestinal symptoms. FDDS diagnosis was carried out according to Rome IV 2016 criteria. Stool character was assessed using the Bristol scale, and clinical symptoms of АT were also analyzed. Results: Bacterial АT was diagnosed in 51.1% (70) of patients and EBV tonsillitis — in 48.9% (67), namely with equal frequency. The incidence of FDDS was 41.6% (95% CI (confidence interval) (33.3, 50.3), including 38.7% in children from 1 to 4 years old (95% CI (24.4, 54.5) and over 4 years 43.0% (95% CI (32.8, 53.7). Functional constipation (25.0%) and functional diarrhea (13.6%) were found in young children, all children over the age of 4 years had abdominal pain (including irritable bowel syndrome with a predominance of constipation — 4.3%). In EBV-RT with FDDS, the incidence of hepatolienal syndrome was 33.3% higher (RR (relative risk) 2.40; 95% CI (1.02, 5.66) and OR (odds ratio) 5.46; 95% CI (1.39, 21.28). Children with FDDS are 22.4% more likely (RR 1.65; 95% CI (1.21, 2.24) and OR 4.1; 95% CI (1.39, 12.07) suffered from recurrent acute respiratory infections; their relatives were more likely to have gastroenterological diseases (RR 1.54; 95% CI (1.12, 2.13) and OR 2.99; 95% CI (1.22, 7.34). Perinatal hypoxic lesions of the central nervous system were more often recorded in patients with FDDS in the anamnesis (RR 1.99; 95% CI (1.25, 3.15) and OR 4.13; 95% CI (1.37, 12.42). Conclusion: The etiological role of EBV among children with exudative АT admitted to the hospital is high. FDDS is more common among children with exudative АT over 4 years of age than in the general pediatric population. The influence of FDDS on the clinical manifestations of EBV-RT is highly probable. It is advisable to continue the study to determine the significance of АT in the development of FDDS in children and adolescents; their results may be useful for clinical practice.